Does husband's alcohol consumption increase the risk of domestic violence during the pregnancy and postpartum periods in Nepalese women? - Narayan Bhatta; Sawitri Assanangkornchai; Ishwari Rajbhandari (BMC, 2021)
Abstract Background Domestic violence against women during pregnancy and the postpartum period not only violates the human rights of women but also harms on the health of both mother and child. Domestic violence is entrenching in social norms, customs and structural factors against women in Nepal. The use of alcohol also exacerbates domestic violence. The objective of this study was to determine the association between domestic violence against women and husband's drinking behavior across the periods of pregnancy and postpartum. Methods This study was a cross-sectional study conducted in the antenatal care and postnatal care clinics of a government hospital in Kathmandu district. Among 660 women (aged 15-49), 165 women were consecutively recruited from each trimester of pregnancy and the postpartum period. Adjusted odds ratios (AOR) were computed from a multivariate logistic regression model to determine the association between domestic violence against women and the husband's drinking behavior. Results Women whose husbands drank alcohol were twice as likely to suffer from domestic violence, compared to those women whose husbands did not drink (AOR = 2.12; 95% CI: 1.4-3.2), independently of their socio-demographic status. Women suffered from domestic violence in each period of pregnancy and postpartum due to their husband's drinking habits, but the most affected period was the second trimester of pregnancy. Among women who suffered from physical, psychological and sexual violence during the pregnancy and postpartum periods, 70.2, 67.9, and 64.2% respectively experienced violence due to their husband's drinking habit. Other associated factors for domestic violence included the ethnic culture of Janjati ethnicity, illiteracy of the women, duration of marriage 2-5 years (compared to one year or less) and a husband who behaved in a controlling manner. Conclusions Having a husband who has alcohol drinking behavior is an important risk factor for domestic violence against women in the pregnancy and postpartum periods. Screening of alcohol use in husbands will not prevent domestic violence but could lead to a referral to integrated treatment for alcohol and domestic violence treatment.